PENGARUH SUBJECTIVE NORM, PERCEIVED USEFULNESS, DAN VIDEO REVIEW PRODUK TERHADAP KEPUTUSAN PEMBELIAN PERALATAN RUMAH TANGGA DI MARKETPLACE DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING - Ketut Dipa Wiguna (Jurnal Ekonomi Manajemen dan Bisnis, 2022)
Shopping for household appliances in the marketplace has become urban Indonesian's lifestyle. In determining the decision to purchase household appliances in the marketplace, there are important variables that influence it. So this study aims to determine how the influence of these variables such as: 1) Subjective norm, perceived usefulness, and product review videos on purchase intention, 2) Subjective norm, perceived usefulness, product review videos, and purchase intention on purchase decisions, 3) Subjective norm, perceived usefulness, and product review videos on purchase decisions through purchase intention as the intervening. This study uses accidental sampling of ITB Asia Malang students. Data were collected using a questionnaire and in total 100 participants responded to the survey. Structural equation modeling (SEM), specifically partial least squares (PLS) was employed to analyze the data. The results of this study indicate that subjective norms, perceived usefulness, and video product reviews have a positive and significant direct effect on purchase intention. Perceived usefulness and purchase intention have a positive and significant direct effect on purchase decisions, while subjective norms and video product reviews have insignificant direct effect on purchase decisions. Purchase intention mediates subjective norms, perceived usefulness, and video reviews positively and significantly towards purchase decisions.